A Collaborative Study to Establish the Second Korean National Reference Standard for Snake Venom - Han, Kiwon; Jung, Kikyung; Oh, Hokyung; Song, Hojin; Park, Sangmi; Kim, Ji-Hye; Min, Garam; Lee, Byung-Hwa; Nam, Hyun-sik; Kim, Yang Jin; Ato, Manabu; Jeong, Jayoung; et al. (Toxicological research (Seoul), 2018)
In 2015, a candidate for the second national reference standard (NRS) of Gloydius snake venom was produced to replace the first NRS of Gloydius snake venom. In the present study, the potencies of the candidate were determined by a collaborative study, and the qualification of the candidate was estimated. The potencies of the candidate were determined by measuring the murine lethal titers and lapine hemorrhagic titers of venom against the regional working reference standard (RWRS) for antivenom using the methods described in the previous report for the first NRS of Gloydius snake venom. Three Korean facilities contributed data from a total of 30 independent assays. Subsequently, two foreign national control research laboratories contributed to this collaborative study. The results were calculated using the Reed-Muench method for lethality and determined using a mixed-effects model for hemorrhage. The general common potencies of the lethal and hemorrhagic titers were obtained from the results of the 30 tests performed at three Korean facilities. The results are expressed in micrograms for 1 test dose (TD) with a 95% confidence interval as follows: a lethal titer of $90.13μg/TD$ (95% confidence interval = $87.39{\sim}92.86μg$) and a hemorrhagic titer of $10.80μg/TD$ (95% confidence interval = $10.46{\sim}11.14μg$). In addition, the candidate preparation showed good quality evaluation according to the results of the quality estimation of the candidate and is judged to be suitable to serve as the Korean NRS for snake venom. In conclusion, the second NRS of Gloydius snake venom was established in this study and will be used for national quality control, including a national lot release test of Korean antivenom products.